Preoperative Radiotherapy (Preop-RT) Improves Pathological Complete Response Rates in Partial Responders (PR) to Primary Systemic Chemotherapy (PST) in Locally Advanced Breast Cancers (LABC) - Agrawal, Sushma; Gupta, Anshika; Chand, Gyan (South Asian Journal of Cancer, 2025)
Preoperative radiotherapy (preop-RT) can be used as one strategy to improve pathological complete response rates in locally advanced breast cancer. Hence, we conducted a pilot study of preop-RT in partial responders to primary systemic chemotherapy (PST).Standard PST comprising of four cycles of Adriamycin/cyclophosphamide followed by four cycles of taxanes (along with trastuzumab in Her2-neu enriched) was initiated. After two cycles of taxanes, partial responders (PRs) were enrolled onto preop-RT (40 Gy/15#/3 weeks to whole breast followed by boost dose of 10 Gy/4#/1 week to gross tumor with 5 mm margin [clinical target volume] and 10 mm margin [planning target volume] by three-dimensional conformal radiation therapy. Field-in-field technique was used whenever the need to correct dose heterogeneity arose. The remaining two cycles of taxanes were completed 3 weeks after the completion of RT. Surgical intervention was initiated 6 weeks after the completion of PST. The intention of such a strategy was to keep an interval of 12 weeks between completion of RT and surgery to achieve maximum downstaging. The primary endpoint was pathological complete response rate (ypCR).Twenty-one women were enrolled (median age 47 years, 35% premenopausal, 50% upper outer quadrant, 65% T4, 85% node positive, 40% luminal A, 10% luminal B, 15% Her-2-neu enriched, and 35% triple-negative breast cancer [TNBC]). Twenty-eight percent underwent breast conservation and the rest modified radical mastectomy (n = 13) and 2 did not undergo surgery (elderly [n = 1], lost to follow-up [n = 1]). ypCR(T) rate was 53% and ypCR(N) was 59%. ypCR(T) rate was 50% in Her-2 positive and 25% in TNBC, and 33.3% in luminal A. At a median follow-up of 24 months, the median overall survival is 41 months and 2 (both TNBC, ypCR, and ypPR) developed distant metastasis (in lung and soft tissue).This pilot study reveals encouraging results in high-risk subsets and this potential of preop-RT should be explored further in larger studies.
Keywords: locally advanced breast cancer; neoadjuvant chemotherapy; preoperative radiotherapy; pathological complete response